INFLUENCE OF IMPURITY Ni AND Cu ATOMS ON THE ELECTROPHYSICAL PROPERTIES OF Si - N. A. Turgunov; E. Kh. Berkinov; R. M. Turmanova (Zeta Repository, 2023)
The paper presents the results of studies of the electrophysical properties of Si, doped Ni and Cu samples.